Evaluating The Effectiveness of Blended Learning during Covid-19 on Students’ Learning Achievement: A Case Study in terms of Islamic Education - Subiyantoro, Subiyantoro (Jurnal Pendidikan Agama Islam, 2022)
Purpose – This study aims to evaluate the effectiveness of blended learning during the Covid-19 pandemic on students’ learning achievements at SMP Muhammadiyah 1 Prambanan. Design/methods/approach – This research was conducted by means of a descriptive qualitative method. The data were collected through observation, interviews and documentation. The collected data were analyzed by reducing data, presenting data, and drawing conclusions. Findings – This study revealed that blended learning had not been able to achieve the desired learning objectives, since it had not been able to reflect the value of Islamic education as seen from students’ lack of manners, particularly to teachers. This fact is attributed to several factors: 1) Teachers’ lack of monitoring on students’ development and associations during the pandemic 2) lack of motivation to learn, 3) lack of adequate facilities for online learning. To overcome the aforementioned problems, teachers have done the followings based on several aspects: 1) the cognitive aspect, the teachers were proactive by helping students who had learning difficulties during the online learning. 2) affective aspects, teacher set an example to students, trained them to practice regular worship, sharpen their ability to behave honestly, and monitored the development of their attitudes and behaviors through their parents. 3) psychomotor aspect, teachers reopened several extracurricular activities. Research limitations – The limitations of this research are mainly centered on the limited number of samples observed as case studies at SMP Muhammadiyah 1 Prambanan. Originality/value – The research findings provide an explanation on the effectiveness of blended learning during the Covid-19 pandemic and teachers’ efforts in achieving learning outcomes.